What are the sources of contraceptives for married and unmarried adolescents: Health services or friends? Analysis of 59 low- and middle-income countries - Hellwig, Franciele; Barros, Aluísio J. D. (Frontiers in Public Health, 2023)
Background Despite the efforts to promote universal coverage for family planning, inequalities are still high in several countries. Our aim was to identify which sources of contraceptives women mostly rely on in low- and middle-income countries (LMICs). We also explored the different sources according to age and marital status. Methods We used data from national health surveys carried out in 59 LMICs since 2010. Among all sexually active women at reproductive age, we explored inequalities in demand for family planning satisfied by modern methods (mDFPS) and in the source of modern contraceptives according to women's age, classified as: 15–19, 20–34, or 35–49 years of age. Among adolescents, mDFPS and source of method were explored by marital status, classified as married or in union and not married nor in a union. Results mDFPS was lower among adolescents than among adult women in 28 of the 59 countries. The lowest levels of mDFPS among adolescents were identified in Albania (6.1%) and Chad (8.2%). According to adolescents' marital status, the pattern of inequalities in mDFPS varied widely between regions, with married and unmarried adolescents showing similar levels of coverage in Latin America and the Caribbean, higher coverage among unmarried adolescents in Africa, and lower coverage among unmarried adolescents in Asia. Public and private health services were the main sources, with a lower share of the public sector among adolescents in almost all countries. The proportion of adolescents who obtained their contraceptives in the public sector was lower among unmarried girls than married ones in 31 of the 38 countries with data. Friends or relatives were a more significant source of contraceptives among unmarried compared to married adolescents in all regions. Conclusions Our findings indicate lower levels of mDFPS and lower use of the public sector by adolescents, especially unmarried girls. More attention is needed to provide high-quality and affordable family planning services for adolescents, especially for those who are not married.